2020
DOI: 10.1002/kjm2.12318
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the long noncoding RNA SNHG1 inhibits tumor cell migration and invasion by sponging miR‐195 through targeting Cdc42 in oesophageal cancer

Abstract: Despite the poor prognosis of oesophageal cancer (EC), the molecular mechanisms of EC are still unclear. In recent years, role of lncRNA in cancer development attracted much attention. The present study aimed to investigate the effects of the long noncoding RNA SNHG1 on the migration and invasion of EC cells and the possible mechanisms involved. The effects of SNHG1 on cell proliferation, migration, and invasion were determined and its relationship with miR‐195/Cdc42 axis was investigated. It was found SNHG1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…20 This study found that CDC42 was highly expressed in CC tissues and was negatively correlated with miR-101-5p expression. Studies have shown that CDC42 is targeted and regulated by miR-195 in esophageal cancer, 35 and in this study, we found that CDC42 was a target gene of miR-101-5p. Further, our results showed that MYLK-AS1 regulated CC progression through the miR-101-5p/CDC42 axis, and knockdown of CDC42 or upregulation of miR-101-5p partially reversed the effects caused by upregulation of MYLK-AS1 is required for WASP/N-wasp activation.…”
Section: Discussionsupporting
confidence: 70%
“…20 This study found that CDC42 was highly expressed in CC tissues and was negatively correlated with miR-101-5p expression. Studies have shown that CDC42 is targeted and regulated by miR-195 in esophageal cancer, 35 and in this study, we found that CDC42 was a target gene of miR-101-5p. Further, our results showed that MYLK-AS1 regulated CC progression through the miR-101-5p/CDC42 axis, and knockdown of CDC42 or upregulation of miR-101-5p partially reversed the effects caused by upregulation of MYLK-AS1 is required for WASP/N-wasp activation.…”
Section: Discussionsupporting
confidence: 70%
“…The lncRNA SNHG1 promotes cervical cancer progression by regulating NIMA-related kinase 2 (NEK2) expression via inhibiting miR-195 [ 32 ]. In addition, SNHG1 enhances cell proliferation, migration and invasion in esophageal cancer by regulating cell division cycle 42 (Cdc42) expression via inhibiting miR-195 [ 33 ]. lncRNA SNHG15 was increased in human cancers and can contribute to cell proliferation by acting as a sponge for miRNAs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of lncRNAs (as ceRNAs) to miRNAs prevents the latter from recognizing their targets, which consequently results in mRNA upregulation. Therefore, during malignant transformation, oncogenic lncRNAs intensify cancer promotion via the downregulation of miRNAs targeting different driver oncogenes (24,25).…”
Section: Introductionmentioning
confidence: 99%